Bioactivity analysis of Sarcolobus globosus Wall., a mangrove plant of the Sundarbans: Bioactivity of S. globosus (Journal of the Bangladesh Agricultural University, 2019)
The aspiring prospect for bioactive metabolites has guided this very study to screen for antioxidant, antibacterial and cytotoxic activities of leaf, and bark extracts of Sundarbans mangrove plant, Sarcolobus globosus that might lead to novel drug, agrochemicals and neutraceuticals. Methanolic bark extract of S. globosus revealed the highest antioxidant properties among all the extracts in DPPH free radical scavenging activity (IC50:26.04 µg/ml), reducing efficiency (EC50:77.72 µg/ml), total phenolic content (47.25 ± 0.002mg GAE/g of extract), total flavonoid content (101 ± 0.003 mg GAE/g of extract) and total tannin content (93.5 ± 0.007 mg GAE/g of extract). Free radical scavenging activity and reducing power are significantly correlated with total phenol, flavonoid and tannin content. For evaluation of antibacterial activity, Gram positive bacteria (Bacillus megaterium, Staphylococcus aureus, and Micrococcus sp.) and Gram negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Vibrio cholerae, Salmonella paratyphi, Pseudomonas sp., and Proteus sp.) were used in disc diffusion bioassay. Both extracts possessed significant (P < 0.05) inhibition competency against most of the bacteria. Test for cytotoxic activity was carried out by means of brine shrimp lethality bioassay and the chloroformic bark extract demonstrated greater cytotoxicity (LC5019.487 µg/ml) than standard vincristine sulphate (LC50 26.68 µg/ml). Further exploration is required focusing especially the bark extract that could be utilized as source and template for the synthesis of new potential pharma and agrochemicals.J Bangladesh Agril Univ 17(4): 476–482, 2019